The Role of OmpR in Bile Tolerance and Pathogenesis of Adherent-Invasive Escherichia coli - Lucchini, Valentina; Sivignon, Adeline; Pieren, Michel; Gitzinger, Marc; Lociuro, Sergio; Barnich, Nicolas; Kemmer, Christian; Trebosc, Vincent (Frontiers in Microbiology, 2021)
Gut microbiota dysbiosis towards adherent-invasive Escherichia coli (AIEC) plays an important role in Crohn’s disease (CD). The OmpR transcriptional regulator is required for the AIEC LF82 prototype strain to adhere and invade intestinal epithelial cells. In this study, we explored the role of OmpR in AIEC pathogenesis using a panel of eight E. coli strains isolated from CD patients and identified as AIEC. The deletion of ompR together with the implementation of two cell-based assays revealed that the role of OmpR in adhesion in vitro was not conserved in AIEC clinical strains. Nevertheless, we showed that OmpR was required for robust gut colonization of transgenic mice expressing human CEACAM receptors, suggesting that OmpR is involved in alternative virulence mechanisms in AIEC strains. We found that deletion of ompR compromised the ability of AIEC strains to cope with the stress induced by bile salts, which may be key for AIEC pathogenesis. More specifically, we demonstrated that OmpR was involved in a tolerance mechanism towards sodium deoxycholate (DOC), one of bile salts main component. We showed that the misregulation of OmpF or the loss of outer membrane integrity are not the drivers of OmpR-mediated DOC tolerance, suggesting that OmpR regulates a specific mechanism enhancing AIEC survival in the presence of DOC. In conclusion, the newly discovered role of OmpR in AIEC bile tolerance suggests that OmpR inhibition would interfere with different aspects of AIEC virulence arsenal and could be an alternative strategy for CD-treatment.